Menopausal hormone therapy and uterine cancer: the acceptability of the tandem - O V Yakushevskaya; S V Yureneva; A E Protasova; G N Khabas; M R Dumanovskaya (IP Berlin A.V., 2018)
The aim of the work is to conduct a systematic analysis of the available research results on the possibility of using menopausal hormone therapy (MHT) in patients who successfully completed the treatment of endometrial cancer (EC). Materials and methods. The review includes data from foreign articles published in PubMed and Medline, and domestic works published on elibrary.ru over the past 40 years. Results. The results obtained allow us to consider MHT as an independent method of medical rehabilitation for women who have undergone EC. A clear patient profile should be established, allowing the use of this method, with strict adherence to health monitoring. Conclusion Patients who have successfully completed the treatment of EC require the creation of special rehabilitation conditions in the interests of maintaining health and quality of life and should be under the close attention of the doctor. Argumented approaches to the appointment of MHT in such patients will avoid complications associated with estrogen deficiency after surgery, radiation with or without systemic (cytostatic) treatment methods.